Characteristics of dynamic geomorphology of coastal-river mouth zones of Ma river of Thanh Hoa province - Quan, Nguyen Cong; Hung, Pham Van (Vietnam Journal of Earth Sciences, 2016)
Reasearch on dynamic geomorphological characteristics of coastal-river mouth zones song Ma of Thanh Hoa areas has an important significance which is useful in using and exploiting rationally the territory and developing sustainably social-economics. Main factors affecting recent dynamic processes in the coastal-river mouth zones song Ma of Thanh Hoa are included: river flows, nearshore currents and active tectonic movements of the earth crust; they control the formation and development of modern topography at the coastal-river mouth zones. Sedimentary accumulating controls formation of banks, bars, mounds, dunes and Holocene-Recent plains at the region of Len and Hoi river mouth. In particular, at Len mouth, high accumulation rate controls forming plains, banks, bars, mounds with seaward aggradational rate of 40-50 m/yr; at Hoi mouth, because the source material of low flow, so deposition weak and mostly along the coast in the north and south of the Hoi mouth. The deposition speed reaches 10m/year. Strong erosional processes are developed at nearshore regions of less dense sediment, small river mouths or no river mouth, or occurence of active faults, such as Lach Truong mouth and in river bank of Hoi mouth. Maximum erosion in Cửa Lach Truong with speed 5-6 m/year; Cua Hoi weaker, erosion rate was only 3-5 m/year.References Nguyễn Văn Cư (chủ biên), 1999: Điều tra cơ bản tài nguyên môi trường nhằm khai thác hợp lí đất hoang hoá các bãi bồi ven biển cửa sông Việt Nam. Đề án điều tra cơ bản cấp nhà nước, Viện Địa lí, Hà Nội. Nguyễn Văn Cư, Phạm Huy Tiến, 2003: Sạt lở bờ biển miền Trung Việt Nam. Nxb. KH&KT Hà Nội, 200trg. Phạm Văn Hùng, Vũ Thị Thu Hoài, 2009: Đặc điểm địa mạo động lực vùng cửa sông ven biển từ cửa Ba Lạt đến cửa Đáy. Tạp chí Các Khoa học về Trái đất, T.31, (3), Hà Nội. Nguyễn Văn Hùng, 2002: Đặc điểm cơ bản của đứt gãy Tân kiến tạo khu vực Tây Bắc. Luận án Tiến sĩ, Viện Địa chất, Hà Nội. Hoàng Ngọc Quang (chủ biên), 2008: Nghiên cứu quản lý tổng hợp tài nguyên và môi trường lưu vực sông Mã. Báo cáo đề tài cấp Bộ Tài nguyên và Môi trường, Hà Nội. Phạm Quang Sơn, Nguyễn Tiến Công, Vũ Thị Thu Hoài, 2007: Diễn biến vùng ven biển các tỉnh Nam Định, Ninh Bình trước và sau khi có công trình thủy điện Hòa Bình qua phân tích thông tin viễn thám và GIS. Tạp chí Các Khoa học về Trái Đất. T.19, 3, tr.267-276. Nguyễn Thế Thôn, 1994:  Chuyển động tân kiến tạo và hiện đại của dải ven biển và ven bờ từ Móng Cái đến Cửa Hội. Tạp chí  Địa Chất, Loạt A, số 223, tr.1-6. Phạm Huy Tiến (chủ biên), 2004: Dự báo hiện tượng xói lở - bồi tụ bờ biển cửa sông và các giải pháp phòng tránh. Báo cáo tổng kết đề tài KHCN cấp Nhà nước KC-09-05. Viện Địa lý, Viện KH&CNVN, Hà Nội.